Zelnate on Arrival Could Decrease the Likelihood of Subsequent Pulls in Suspect Bovine Respiratory Disease Complex Cases - T. Spore; S. P. Montgomery; G. A. Hanzlicek; W. R. Hollenbeck; R. N. Wahl; J. E. Sears; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2017)
Antimicrobial metaphylaxis is an important tool used for the prevention of Bovine Respiratory Disease Complex; a disease with a large economic impact that typically affects newly-weaned beef calves that are marketed and transported a distance from their origin. There are questions involving the potential benefit of Zelnate, a novel non-antibiotic technology designed to activate an animal’s natural immunity to fight Bovine Respiratory Disease Complex, being used either solely or in combination with metaphylaxis at the time of initial processing of high risk calves. More knowledge is also needed regarding the possible effects of repeated use of Zelnate when subsequent therapy is required in individual Bovine Respiratory Disease Complex cases. The objective of this study was to evaluate the effectiveness of Zelnate when used as part of an antimicrobial metaphylaxis treatment or when used in combination with an antibiotic when a calf is diagnosed with Bovine Respiratory Disease Complex.
Keywords: Zelnate; high risk; bovine respiratory disease